1998
DOI: 10.1002/(sici)1521-3803(199802)42:01<42::aid-food42>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between environmental pollution in Manzala Lake and health profile of fishermen

Abstract: Manzala Lake exposed to many pollutants including untreated sewage, agricultural and industrial wastes which increase the concentration of heavy metals, and compromise the health state of the fishermen. This study investigated 100 fishermen and 100 males of other occupations as controls. Both groups work in and live on and around the lake. Clinical examination revealed no significant changes between the fishermen and control group as regards the cardiovascular, gastrointestinal and dermatological systems. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…For instance, children and adolescents from highly polluted areas of Cairo have serum cadmium levels higher than those of U.S. children (Samir et al 1997;Hossny et al 2001). Moreover, residents of Dakahleia Province and fishermen of the Manzala Lagoon have serum levels 15 and 30 times higher, respectively, than those of the Cairo residents (Samir et al 1997;Osfor et al 1998b;Hossny et al 2001).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, children and adolescents from highly polluted areas of Cairo have serum cadmium levels higher than those of U.S. children (Samir et al 1997;Hossny et al 2001). Moreover, residents of Dakahleia Province and fishermen of the Manzala Lagoon have serum levels 15 and 30 times higher, respectively, than those of the Cairo residents (Samir et al 1997;Osfor et al 1998b;Hossny et al 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, cadmium levels are high not only in the soil of the Manzala region but also in the sera of fishermen and other apparently healthy residents there (Osfor et al 1998b). Moreover, these high serum levels are even much higher than serum levels of populations in other parts of Egypt.…”
Section: Discussionmentioning
confidence: 98%
“…However, Toda et al (1984) did not ®nd any abnormalities in liver function tests (including AST and ALT) among workers who had been exposed to Cd: Cd levels in urine were elevated up to 185 lg/day, and urinary b 2 -microglobulin levels were also elevated up to 2000 lg/l. In a recent report on the pollution of Lake Manzala in the Nile Delta, Egypt, Osfor et al (1998) reported elevations of AST and ALT in the serum of ®shermen, whose Cd-B levels were found to be higher than those of controls. It is, however, dicult to clarify whether Cd exposure as responsible for the observed AST and ALT elevation, because the lake water as also contaminated with other metals, as well as other pollutants.…”
Section: Discussionmentioning
confidence: 98%
“…It is, however, dicult to clarify whether Cd exposure as responsible for the observed AST and ALT elevation, because the lake water as also contaminated with other metals, as well as other pollutants. Thus, Osfor et al (1998) pointed to possible biological causes such as poor nutrition and infection in addition to exposure to liver toxins. Overall therefore, it is prudent to conclude that the current level of environmental exposure to Cd in Japan is unlikely to induce adverse eects on liver function.…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of heavy metals, including cadmium, are among the pollutants in the water. Plants and fish grown in this water are also contaminated with heavy metals (8,9), which can in turn accumulate in humans and animals that feed on these contaminated foods (10). The serum cadmium levels of residents of Dakahlia Province are almost 10 folds higher than those of residents from cadmium-polluted areas in Cairo and 32 times higher than reference levels for healthy populations in the United States (10)(11)(12).…”
Section: Introduction Introductionmentioning
confidence: 99%